Efficacy of distal perigastric lymphadenectomy for Siewert type II adenocarcinoma of the esophagogastric junction - Li, Zonglin; Liu, Yi; Jiang, Yifan; Song, Min (Frontiers in Surgery, 2025)
BackgroundTo investigate the metastatic rates of distal perigastric lymph nodes (DPLN), including No.3b, 4d, 5, 6 and 12a LN stations, and to evaluate the clinical significance of DPLN lymphadenectomy for patients with Siewert type II adenocarcinoma of the esophagogastric junction (AEG).MethodsFrom January 2014 to December 2018, 217 patients with Siewert type II AEG who underwent total gastrectomy (TG) or proximal gastrectomy (PG) were retrospectively included. Based on clinicopathological data from TG patients, the metastatic rates and the therapeutic value (TV) indexes of DPLN, along with risk factors for DPLN metastasis, were assessed. Additionally, the 5-year overall survival (OS) rates were compared between TG and PG patients.ResultsThe metastatic rates of No.3b, 4d, 5, 6, 12a LN stations and DPLN were 31.7%, 9.6%, 12.6%, 4.0%, 3.1% and 36.4%, whereas the 5-year TV indexes of them were 10.3, 0.0, 1.5, 0.0, 0.0 and 9.7, respectively. Tumor size (>4 cm), pT stage (pT4) and pN stage (pN3) were significant risk factors for patients with DPLN metastasis. For patients with tumor size larger than 4 cm, pT4 stage or pN3 stage, TG was associated with a better prognosis than PG, with the 5-year OS rates of 33.5% and 16.8%, respectively (χ2 = 4.299, p = 0.038).ConclusionsDPLN metastasis is a poor prognostic factor for patients with Siewert type II AEG. For high-risk patients with tumor size larger than 4 cm, cT4 stage or extensive LN metastasis identified preoperatively or intraoperatively, it is recommended to perform TG with expanded lymphadenectomy, including resection of DPLN.